Preliminary rolling noise measurements toward the design of a standard rolling noise device. Issue 1 (March 2022) - Edwards, Matthew; Gonzalez Diaz, Raimundo; Dallaji, Nadia; Jaouen, Luc; Chevillotte, Fabien; Totaro, Nicolas
The tapping machine has long existed as the primary standard method for measuring the performance of floors in buildings in response to structure-borne noise. However, other sources of structure-borne noise exist. One of these is rolling noise: such as a trolley rolling across the floor in an indoor building environment. Because the sound profile of indoor rolling noise is substantially different than that of impact noise, the techniques developed to reduce the latter may not necessarily be effective at reducing the former. To this end, a means of repeatably measuring indoor rolling noise is needed. Here the results of a study on indoor rolling noise are presented, identifying the various characteristics of this type of excitation which until now have been left unexplored. The proposal for a standard rolling device is also put forth: a machine which may be capable of characterizing a floor's performance with regards to indoor rolling noise. A series of indoor rolling noise tests were conducted in order to characterize the range of sound profiles that various indoor rolling items are capable of producing, as well as identify how the different characteristics govern the shape of the sound profile produced. Just as the standard tapping machine assesses a floor's performance in response to impact noise, a standard rolling machine may assess a floor's performance in response to rolling noise.